2007
DOI: 10.1007/s10597-006-9074-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatrists’ Smoking Cessation Activities with Ohio Community Mental Health Center Patients

Abstract: This study describes a survey of Ohio community mental health center psychiatrists' perceptions and practices regarding smoking cessation activities using the 5A's method of smoking cessation. Of the 150 psychiatrists surveyed, 80 (53%) were returned. The majority of psychiatrists reported asking their patients about cigarette smoking status as well as giving advice to quit. However, the practice of actually facilitating quit attempts (i.e. with social support, nicotine replacement therapy, referrals, and foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 40 publications
4
36
2
1
Order By: Relevance
“…For instance, previous research has identified that some hold concerns that patients' mental health or abstinence will suffer 14, 15, 16, 17 and that smokers are unable 18 or unmotivated to quit 19. This is in contrast to evidence that smoking cessation, if not actually benefitting mental health, does not impact mental health negatively in people with or without psychiatric disorders 20, even in life‐long, long‐term smokers 21, and that smokers with mental illnesses are just as likely to want to quit as smokers without 22.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, previous research has identified that some hold concerns that patients' mental health or abstinence will suffer 14, 15, 16, 17 and that smokers are unable 18 or unmotivated to quit 19. This is in contrast to evidence that smoking cessation, if not actually benefitting mental health, does not impact mental health negatively in people with or without psychiatric disorders 20, even in life‐long, long‐term smokers 21, and that smokers with mental illnesses are just as likely to want to quit as smokers without 22.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to evidence that smoking cessation, if not actually benefitting mental health, does not impact mental health negatively in people with or without psychiatric disorders 20, even in life‐long, long‐term smokers 21, and that smokers with mental illnesses are just as likely to want to quit as smokers without 22. MHPs have also been reported to hold permissive attitudes towards smoking, such as the belief that smoking with patients can help build a therapeutic relationship 15, 23, 24 and that allowing patients to smoke ensures a smoother running of wards in in‐patient settings 19.…”
Section: Introductionmentioning
confidence: 99%
“…Despite commonly held misconceptions amongst mental health professionals that clients are not motivated, or willing to quit smoking, or that tobacco smoking may manage or reduce the symptoms of mental illness (Lawn, 2004;Price, Ambrosetti, Sidani, & Price, 2007;RCP&RCP, 2013;Wye et al, 2010b), recent research has indicated otherwise (RCP&RCP, 2013;Stockings et al, 2013). Further, recent research suggests that smokers with a mental illnesss would find it acceptable to be provided with smoking cessation care by the health and community services they currently utilise for mental health care (Bartlem et al, 2015;Ferron, Brunette, He, McHugo, & Drake, 2011;Stockings et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The latter findings contrast with the particular importance of referral and follow-up care in ensuring successful change in health risk behaviors. 48,53,54 The low levels of referral found in this study may be related to a number of possible barriers, including difficulties for clients in accessing a general practitioner or primary care physician [55][56][57] ; poor communication between mental health services, primary care, and other referral services 58,59 ; clinician perceptions that clients would not be responsive to behavior change [58][59][60][61] ; and a perceived lack of referral options. 58,[61][62][63] Despite such perceptions, evidence-based and readily accessible referral options (free government services) are available for clinician referral regarding smoking cessation (www.icanquit.com.au/further-resources/quitline) and inadequate nutrition and physical activity (www.…”
Section: Discussionmentioning
confidence: 95%